Pembuatan Japanese Fruit Sandwich bagi Masyarakat Kelurahan Padang Masiang Kecamatan Barus Kabupaten Tapanuli Tengah - Jeniusman Ahmad Hutagalung; Heriyawan Hutagalung; Fauziah Nur Simamora; Mhd. Safwan Koto (COVIT (Community Service of Health), 2023)
The objectives of implementing this community partnership program (PKM) service are (1) understanding PKM in the midst of the Padang Masiang Village community, (2) understanding in making Japanese fruit sandwiches in the midst of the Padang Masiang urban village community, (3) understanding the importance of developing economic potential in Padang Masiang Village. sir . The method for implementing Japanese fruit sandwich making activities includes several stages, namely: (1) Introduction Stage, (2) Socialization and Audience Stage, (3) Japanese fruit sandwich making training stage. 4) Final Evaluation Stage. The result of this activity is that the community knows how to make Japanese fruit sandwiches and can improve the economy in the Padang Masiang sub-district. The PKM community service partner is Padang Masiang Village, Barus District, Central Tapanuli Regency. This program is carried out as one of the efforts to add insight to the community in improving the economy of the surrounding community. Keywords: Fruit, Making, Sandwich